TWO-STAGE DECOMPOSITION OF KYZYLCUM PHOSPHATE TO PRODUCE A GRANULATED SIMPLE SUPERPHOSPHATE IN AN ANHYDRITE MODE (Journal of Pharmaceutical Negative Results, 2022)
It has been determined that the main phosphate mineral of Kyzylkum granular phosphate is the Francolite. Calcite, dolomite, gypsum, quartz, calcium silicate, etc. Sulfuric acid has been calculated to decompose the dried concentrate (25.75% P2O5) to produce a simple superphosphate (at least 17% P2O5). The distinctive feature of the proposed flow method before the classical (chamber) method is that the entire production cycle for processing natural phosphate is carried out in two stages. At the 1st stage, the phosphate raw material is treated with a stoichiometric consumption of concentrated sulfuric acid (at least 93%), under conditions of complete decomposition of the dried concentrate with the formation of phosphoric acid and anhydrite crystals (calcium sulfate). In this case, the reaction temperature is 130 °C. At the second stage, the formed concentrated solution of phosphoric acid in a mixture with sulphuric participates in the reaction with an additional injectable amount of dried concentrate, This is the basis for the chemical formation of monocalcium phosphate and the granulation of the superphosphate mass. In comparison with the classical scheme, the stages of storage maturation, ammonization and drying of the product are excluded from the process.